Systematic literature review supported VOSviewer: Geothermal energy as an alternative energy in Indonesia - Anisa Ayu Solikah; Sulistyo Saputro; Sentot Budi Rahardjo (Journal of Energy, Mechanical, Material, and Manufacturing Engineering, 2023)
The need for electricity in Indonesia is still high due to its population and large area. However, power plant fuels such as coal are less able to meet the electricity needs in the community. This is because the amount of coal is running low and cannot be renewed. To overcome this, the government focuses on developing power plants from alternative energy that is new renewable so that it will not run out. To achieve this goal, studies are needed that can inform the public and researchers in the future. The study of geothermal energy as an alternative energy for power plants in Indonesia from 2013-2023 aims to provide information and analysis related to obtain: 1) the principle of changing geothermal energy into electrical energy. 2)The use of geothermal energy in the world today. 3)The research on the use of geothermal energy so far in Indonesia? 4) The potential of geothermal energy as an alternative power plant for Indonesia? The research on the use of geothermal energy so far in Indonesia through literature review and supported by VOSviewer, 5) The challenges and solutions in developing geothermal energy as an alternative to power generation in Indonesia.